2008
DOI: 10.1530/eje-07-0768
|View full text |Cite
|
Sign up to set email alerts
|

Repeated administration of ghrelin to patients with functional dyspepsia: its effects on food intake and appetite.

Abstract: Background: Ghrelin plays a major role in the regulation of food intake (FI), which makes it a strong candidate for the treatment of anorexia. Objective: We attempted to evaluate the clinical response to repeated ghrelin administration in patients with anorexia caused by functional disorders, such as functional dyspepsia (FD). Subjects and methods: Subjects included in this study were those who 1) were diagnosed with functional anorexia, including FD and other eating disorders with the exception of anorexia ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(42 citation statements)
references
References 29 publications
1
40
0
Order By: Relevance
“…Plasma acyl ghrelin levels correlated with "subjective symptom score" in female patients with functional dyspepsia (Shinomiya et al, 2005), whereas plasma acyl and total ghrelin levels correlated with "ingestive score" in another group of patients with functional dyspepsia (Nishizawa et al, 2006). Repeated intravenous administration of acyl ghrelin tended to increase daily food intake and significantly induced hunger sensation in patients with functional dyspepsia (Akamizu et al, 2008).…”
Section: G Total Acyl Ghrelin and Functional Dyspepsiamentioning
confidence: 91%
“…Plasma acyl ghrelin levels correlated with "subjective symptom score" in female patients with functional dyspepsia (Shinomiya et al, 2005), whereas plasma acyl and total ghrelin levels correlated with "ingestive score" in another group of patients with functional dyspepsia (Nishizawa et al, 2006). Repeated intravenous administration of acyl ghrelin tended to increase daily food intake and significantly induced hunger sensation in patients with functional dyspepsia (Akamizu et al, 2008).…”
Section: G Total Acyl Ghrelin and Functional Dyspepsiamentioning
confidence: 91%
“…In previous studies, T 1/2 liq (half-emptying time for liquids, in minutes) decreased by 20-30% following injection of 0.7-5.9 µg/kg of ghrelin. We previously reported that ghrelin tended to increase appetite in a dose-dependent manner (i.e., more so at 5.0 than 1.0 µg/kg) in a phase I study, and that it is safe at a dose of 5.0 µg/kg [27,28,31]. Based on these findings, we adopted the present protocol.…”
Section: Discussionmentioning
confidence: 98%
“…Visual analogue scale (VAS) scores, 10 cm in length, were used to assess satiety [27][28][29]. VASs were completed pre-infusion and 15, 30, 60, and 90 min after ghrelin or saline administration.…”
Section: Assessment Of Satietymentioning
confidence: 99%
“…Akamizu et al reported the ability of repeated ghrelin administration to increase appetite and food intake in patients with FD (45). Recently, the acyltransferase responsible for ghrelin acylation, GOAT, was discovered (42).…”
Section: Discussionmentioning
confidence: 99%
“…Considering the present results and those of a previous study, ghrelin administration may be more useful for therapy in certain FD patients expressing the preproghrelin 3056TT genotype. The relationship between the ghrelin signaling system and eating behavior makes identifies ghrelin, growth hormone secretagogue receptor (GHSR) and GOAT as good candidate genes for hunger sensation and the risk of eating disorders (45,48).…”
Section: Discussionmentioning
confidence: 99%